Modulation of vagal tone enhances gastroduodenal motility and reduces somatic pain sensitivity. Issue 4 (4th January 2016) - Frøkjær, J. B.; Bergmann, S.; Brock, C.; Madzak, A.; Farmer, A. D.; Ellrich, J.; Drewes, A. M.
Abstract: Background: The parasympathetic nervous system, whose main neural substrate is the vagus nerve, exerts a fundamental antinociceptive role and influences gastrointestinal sensori‐motor function. Our research question was to whether combined electrical and physiological modulation of vagal tone, using transcutaneous electrical vagal nerve stimulation (t‐VNS) and deep slow breathing (DSB) respectively, could increase musculoskeletal pain thresholds and enhance gastroduodenal motility in healthy subjects. Methods: Eighteen healthy subjects were randomized to a subject‐blinded, sham‐controlled, cross‐over study with an active protocol including stimulation of auricular branch of the vagus nerve, and breathing at full inspiratory capacity and forced full expiration. Recording of cardiac derived parameters including cardiac vagal tone, moderate pain thresholds to muscle, and bone pressure algometry, conditioned pain modulation using a cold pressor test and a liquid meal ultrasonographic gastroduodenal motility test were performed. Key Results: Cardiac vagal tone increased during active treatment with t‐VNS and DSB compared to sham ( p = 0.009). In comparison to sham, thresholds to bone pain increased ( p = 0.001), frequency of antral contractions increased ( p = 0.004) and gastroduodenal motility index increased ( p = 0.016) with active treatment. However, no effect on muscle pain thresholds and conditioned pain modulation was seen. Conclusions & Inferences: This experimental study suggests that this noninvasive approach with combined electrical and physiological modulation of vagal tone enhances gastroduodenal motility and reduces somatic pain sensitivity. These findings warrant further investigation in patients with disorders characterized with chronic pain and gastrointestinal dysmotility such as functional dyspepsia and irritable bowel syndrome. Abstract : The aim was to explore the effect of combined electrical and physiological modulation of vagal tone on musculoskeletal pain thresholds and gastroduodenal motility. Cardiac vagal tone, thresholds to bone pain, frequency of antral contractions, and gastroduodenal motility index all increased during active treatment compared to sham.